2017
DOI: 10.1088/1612-202x/aa6515
|View full text |Cite
|
Sign up to set email alerts
|

The shift of harmonics with different initial vibrational states in the H${}_{2}^{+}$ molecular ion

Abstract: Molecular high-order harmonic generation of H + 2 and its isotopes is investigated by numerical simulations of the non-Born-Oppenheimer time-dependent Schrödinger equations. The general characteristic of the typical high-order harmonic generation (HHG) spectra for the H + 2 molecule indicates that only the odd harmonics can be generated. Here we show that how the initial vibrational states and nuclear dynamics break down this standard characteristic, i.e. a redshift or blueshift of the harmonics appears. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…[16] Morales et al [17] investigated the electron localization on the HHG, and found that the even-order harmonic generation can be observed. The shift of HHG spectrum with variational initial vibrational states was reported, [18] the redshift and blueshift of HHG can be controlled by changing the initial vibrational state, and the shift of the HHG spectrum can be observed by increasing the nuclear distance R.…”
Section: Introductionmentioning
confidence: 95%
“…[16] Morales et al [17] investigated the electron localization on the HHG, and found that the even-order harmonic generation can be observed. The shift of HHG spectrum with variational initial vibrational states was reported, [18] the redshift and blueshift of HHG can be controlled by changing the initial vibrational state, and the shift of the HHG spectrum can be observed by increasing the nuclear distance R.…”
Section: Introductionmentioning
confidence: 95%
“…Through the time-frequency analysis, it is indicated that the spectral redshift can be observed when a weak VUV pulse is added in the falling part of the fundamental pulse. The relationship between the harmonic instantaneous frequency and the laser field intensity is given by ω q (t) = qω + α q [∂ I(t)/∂t], [23,24] where ω 0 is the frequency of the laser field, q is the harmonic order. In the rising part of the laser field, the amplitude of continuous laser cycles is larger than that of the previous laser cycle, ∂ I(t)/∂t > 0.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by increasing the intensity of the second pump pulse, the population of the 3dσ g state is greatly enhanced and the related dependence of harmonic spectra on the delay time between the second pump pulse and the probe pulse exhibits an obvious redshift. As a frequency modulation of HHG spectra, the redshift has attracted more attention due to its stableness of probing the nuclear motion [25][26][27][28][29]. Both for the parallel orientated resonant system based on the BOA [12] and for the arbitrary aligned nonresonant system based on the NBOA [26], the redshift can be observed.…”
mentioning
confidence: 99%
“…Both for the parallel orientated resonant system based on the BOA [12] and for the arbitrary aligned nonresonant system based on the NBOA [26], the redshift can be observed. Moreover, Liu et al revealed the variation of the harmonics from redshift to blueshift with the enhancement of the initial vibrational state for H + 2 [27]. For the molecular system in the single electronic state, the redshift was generally viewed as the frequency modulation of intercycle HHG dynamics on the falling edge of the intense laser field [25][26][27][28][29].…”
mentioning
confidence: 99%
See 1 more Smart Citation